Study protocol for a multicentre, randomised controlled trial to compare the use of the decellularised dermis allograft in addition to standard care versus standard care alone for the treatment of venous leg ulceration: DAVE trial - John Norrie; Sarrah Peerbux; Nicky Cullum; Akila Chandrasekar; Richard Lomas; Andrew Bradbury; Karen Dhillon; Sarah Onida; Francine Heatley; Layla Bolton; Tristan Lane; David Epstein; et al. (BMJ Open)
Introduction Venous leg ulceration (VLU), the most common type of chronic ulcer, can be difficult to heal and is a major cause of morbidity and reduced quality of life. Although compression bandaging is the principal treatment, it is time-consuming and bandage application requires specific training. There is evidence that intervention on superficial venous incompetence can help ulcer healing and recurrence, but this is not accessible to all patients. Hence, new treatments are required to address these chronic wounds. One possible adjuvant treatment for VLU is human decellularised dermis (DCD), a type of skin graft derived from skin from deceased tissue donors. Although DCD has the potential to promote ulcer healing, there is a paucity of data for its use in patients with VLU.Methods and analysis This is a multicentre, parallel group, pragmatic randomised controlled trial. One hundred and ninety-six patients with VLU will be randomly assigned to receive either the DCD allograft in addition to standard care or standard care alone. The primary outcome is the proportion of participants with a healed index ulcer at 12 weeks post-randomisation in each treatment arm. Secondary outcomes include the time to index ulcer healing and the proportion of participants with a healed index ulcer at 12 months. Changes in quality of life scores and cost-effectiveness will also be assessed. All analyses will be carried out on an intention-to-treat (ITT) basis. A mixed-effects, logistic regression on the outcome of the proportion of those with the index ulcer healed at 12 weeks will be performed. Secondary outcomes will be assessed using various statistical models appropriate to the distribution and nature of these outcomes.Ethics and dissemination Ethical approval was granted by the Bloomsbury Research Ethics Committee (19/LO/1271). Findings will be published in a peer-reviewed journal and presented at national and international conferences.Trial registration number ISRCTN21541209.